Biometric Security and Privacy Opportunities & Challenges in The Big Data Era - Jiang, Richard; Al-maadeed, Somaya; Bouridane, Ahmed; Crookes, Prof. Danny; Beghdadi, Azeddine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book highlights recent research advances on biometrics using new methods such as deep learning, nonlinear graph embedding, fuzzy approaches, and ensemble learning. Included are special biometric technologies related to privacy and security issues, such as quality issue, biometric template protection, and anti-spoofing. The book also focuses on several emerging topics such as big data issues, mobile biometrics and multispectral biometrics, and includes a number of new biometrics such as vein pattern, acoustic biometrics, eye-blinking EOG, ECG, gait and handwriting. Authors also show how to use biometrics in cyber security applications and its relevant legal matters under EU legislation. The contributors cover the topics, their methods, and their applications in depth.
Introduction -- Part I - New Methods in Biometrics -- Deep Biometrics: A Robust Approach to Biometrics in Big Data Issues -- Multimodal Biometric Fusion via Ensemble Learning -- Fuzzy Logic for Precise Biometric Systems -- Hierarchical Biometric Verification with Sparse Features -- Dynamic Programming for Biometric Verification -- Part II - New Advances in Various Biometric Technologies -- Paleographic Handwriting Analysis for Author Identification -- Palmprints versus Fingerprints: Rivals or Friends? -- A Survey on Soft Biometrics for Forensic Analysis -- Robust Biometric Verification with Low Quality Data -- Streamed Biometric Verification for Big Data Challenge -- Privacy-Protected Biometric Verification for Security Applications -- Part III - New Applications using Biometrics -- Biometric Key Generation using Fuzzy Extractor for Mobile Banking -- Securing Electronic Medical Records Using Biometric Authentication -- Body Biometrics from MRI Images for Medicine Advice -- Identify Invisible Persons inSocial Network -- From Memory to Human Recognition in Cognitive Robots.
Keywords: Signal processing; Biometric identification; Quantitative research; User interfaces (Computer systems).; Human-computer interaction; Security systems; Data protection; Signal, Speech and Image Processing; Biometrics; Data Analysis and Big Data; User Interfaces and Human Computer Interaction; Security Science and Technology; Data and Information Security